Radiation Therapy for Low-Risk Breast Cancer: Whole, Partial, or None?. Issue 36 (20th December 2022) - Moran, Meena S.; Ho, Alice Y.
Abstract : The Oncology Grand Rounds series is designed to place original reports published in the Journal into clinical context. A case presentation is followed by a description of diagnostic and management challenges, a review of the relevant literature, and a summary of the authors' suggested management approaches. The goal of this series is to help readers better understand how to apply the results of key studies, including those published in Journal of Clinical Oncology, to patients seen in their own clinical practice . The following case represents a relatively common clinical scenario of a postmenopausal female patient who presents with low-risk, estrogen receptor–positive/progesterone receptor–positive/human epidermal growth factor receptor 2–negative, early-stage, left-sided breast cancer to discuss the role of postoperative radiation (RT) following wide local excision (WLE) and sentinel node biopsy. The spectrum of choices, ranging from omission of RT, accelerated partial breast irradiation (PBI), whole-breast radiation therapy, and the nuances of various dose/fractionation regimens for each option, are discussed in the context of the Danish Breast Cancer Study Group (DBCSG) PBI trial published in this issue, with additional review of other key trials that inform these treatment recommendations. After consideration of the clinical-pathologic features in the framework of the existing data and an in-depth discussion taking into consideration the patient's preferences/goals, the decision was made to deliver moderately hypofractionated RT (40 Gy/15 fractions) to a PBI volume, in concordance with the DBCSG-PBI trial.